Assistance and Mental Strengthening for Women and Child Victims of Sexual Violence through Picture Cards to Reduce Anxiety - Desy Ayu Ningrum; Aas Siti Sholichah (Bulletin of Counseling and Psychotherapy, 2026)
This research was conducted based on the increasing cases of violence against women and children, which often cause psychological impacts, particularly anxiety among victims. Therefore, appropriate mentoring and mental health strengthening strategies are needed to help children express emotions and reduce anxiety effectively. This research aims to determine the results of mentoring and strengthening the mental health of women and child victims of violence through picture cards to reduce anxiety in the city of South Tangerang, Indonesia. This research uses a research method based on Participatory Action Research (PAR), a research method that involves active participation from the community or target group in each stage of the research, considering collaboration between researchers and participants (P2TP2A volunteers and parents) to jointly identify problems, design interventions, take action, and reflect on the results. Data collection for preliminary study activities was carried out through interviews and observation methods with 15 children and parents who had children aged 5-12 years at the Women's Empowerment Service, Child Protection, Population Control and Family Planning (DP3AP2KB), South Tangerang City. The results of the research explain that picture cards used to identify victims of violence against women and children can help reduce anxiety. The media developed picture cards that help children express their anxiety through stories. The picture card media consists of two groups. The first group consists of seven cards used to identify children's anxiety, while the second group consists of six cards containing strategies for reducing anxiety. The images on the picture cards are based on anxiety grids and anxiety theories. The anxiety material written in the guidebook also helps parents understand anxiety more deeply. With language that can be directly conveyed to children, it becomes easier for parents to deliver the material, and the anxiety strategy cards have been developed to teach activities that can help children reduce anxiety.